2020
DOI: 10.1101/2020.01.27.921239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ASC oligomer favor caspase-1CARDdomain recruitment after intracellular potassium efflux

Abstract: Signaling through the inflammasome is important for the inflammatory response. Low concentrations of intracellular K + are associated with the specific oligomerization and activation of the NLRP3 inflammasome, a type of inflammasome involved in sterile inflammation. Subsequent to NLRP3 oligomerization, ASC protein binds and form oligomeric filaments culminating in large protein complexes named ASC specks. ASC specks are also initiated from different inflammasome scaffolds, as AIM2, NLRC4 or Pyrin. ASC oligomer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Although Cl − efflux was required to form an ASC speck, K + efflux was required to permit activation of caspase‐1 (Green et al, 2018). These previous findings are supported by recent research which demonstrated low intracellular K + levels trigger a conformational change in ASC oligomer structure resulting in enhanced caspase‐1 recruitment and activation (Martín‐Sánchez et al, 2020). In the present study, we show that inhibition of K2P channels, non‐selective K + channel inhibition, and K + efflux blockage, all inhibited caspase‐1 activation without blocking the formation of NLRP3‐dependent ASC specks in response to ATP.…”
Section: Discussionsupporting
confidence: 63%
“…Although Cl − efflux was required to form an ASC speck, K + efflux was required to permit activation of caspase‐1 (Green et al, 2018). These previous findings are supported by recent research which demonstrated low intracellular K + levels trigger a conformational change in ASC oligomer structure resulting in enhanced caspase‐1 recruitment and activation (Martín‐Sánchez et al, 2020). In the present study, we show that inhibition of K2P channels, non‐selective K + channel inhibition, and K + efflux blockage, all inhibited caspase‐1 activation without blocking the formation of NLRP3‐dependent ASC specks in response to ATP.…”
Section: Discussionsupporting
confidence: 63%
“…A low extracellular K + concentration has been shown to stimulate conformational changes in the NLRP3 receptor protein and NLRP3 inflammasome activation whereas a high extracellular K + concentration (over 50 mM) prevents the activation, suggesting that K + efflux plays a crucial role in the assembly of the NLRP3 inflammasome complex (Mariathasan et al, 2006;Muñoz-Planillo et al, 2013;Pétrilli et al, 2007;Tapia-Abellan et al, 2021). Recently, a low level of intracellular K + was reported to affect also the structure of ASC specks and further facilitate the CARD domain of ASC to recruit the CARD domain of caspase-1 during the assembly of the inflammasome complex (Martín-Sánchez et al, 2023).…”
Section: Mechanisms Of Nlrp3 Inflammasome Assemblymentioning
confidence: 99%
“…In cells, ASC specks were visualized by microscopy using immunofluorescence or expression of ASC tagged with a fluorescent protein. Upon overexpression, the resulting speck was typically much larger than 1 µm and occasionally showed filaments protruding from the edge of the structure 20,[22][23][24][25] . In contrast, diffractionlimited immunofluorescence imaging of the endogenous ASC speck revealed a spot of about 1 µm in diameter.…”
Section: Introductionmentioning
confidence: 99%